2016
DOI: 10.1016/j.eatbeh.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-monitoring in the maintenance of weight loss success

Abstract: Introduction Self-monitoring has been shown to be a crucial part of initial weight loss success in behavioral interventions. However, little is known about the impact of self-monitoring during the period following initial treatment. Methods The current study examined the role of self-monitoring on weight loss during an initial 6-month intervention period (Phase1) and a 12-month extended care period (Phase 2) in a group of 167 obese women (M±SD: BMI = 37.0±5.1 kg/m2, age = 59.9±6.2 years) enrolled in a behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…In their study, participants were clustered based on percent weight change during a 6‐month intervention period and a 12‐month extended care period. In accordance with our findings, three weight loss patterns were identified, with low, moderate and high rates of weight loss success . Szabo‐Reed et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In their study, participants were clustered based on percent weight change during a 6‐month intervention period and a 12‐month extended care period. In accordance with our findings, three weight loss patterns were identified, with low, moderate and high rates of weight loss success . Szabo‐Reed et al .…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with our findings, three weight loss patterns were identified, with low, moderate and high rates of weight loss success. 27 Szabo-Reed et al used latent profile analysis to identify profiles for weight change over an 18-month follow up. The profiles were described as 'modest loss-complete regain', 'intermediate loss-minimal regain' and 'substantial loss-minimal regain'.…”
Section: Discussionmentioning
confidence: 99%
“…N = 36; includes the three participants who were not part of the analytic sample), although the absolute difference between groups in this reported outcome remained similar. Although daily self-weighing has been demonstrated to improve weight losses in other studies (45) and appears to have a particular role in facilitating weight maintenance (51), the level of self-weighing resulting from the enhanced intervention did not translate to better weight-loss outcomes. Participants and partners treated together in a previous study identified the bodyweight scales provided as very helpful for their weight loss (13).…”
Section: Discussionmentioning
confidence: 82%
“…Attendance at treatment sessions is anticipated to decline over time, but, in keeping with prior studies in the weight control literature, those who attend more sessions are expected to have better weight loss outcomes [ 59 , 60 ]. Adherence to self-monitoring, a known predictor of treatment success [ 61 , 62 ], will be assessed by tracking the total number of self-monitoring diaries that are completed and turned into the group leader during the interventions.…”
Section: Methodsmentioning
confidence: 99%